Oral Route Driven Acute Trypanosoma cruzi Infection Unravels an IL-6 Dependent Hemostatic Derangement - Antunes, Dina; Marins-Dos-Santos, Alessandro; Ramos, Mariana Tavares; Mascarenhas, Barbara Angelica S.; Moreira, Carlos José de Carvalho; Farias-de-Oliveira, Désio Aurélio; Savino, Wilson; Monteiro, Robson Q.; de Meis, Juliana (Frontiers in Immunology, 2019)
Oral transmission of Trypanosoma cruzi, the etiologic agent of Chagas disease, is presently the most important route of infection in Brazilian Amazon. Other South American countries have also reported outbreaks of acute Chagas disease associated with food consumption. A conspicuous feature of this route of transmission is presenting distinct symptoms such as facial and lower limbs edema, in some cases bleeding manifestations and risk of thromboembolism are evident. Notwithstanding, studies that address this route of infection are largely lacking regarding its pathogenesis and, more specifically, the crosstalk between immune and hemostatic systems. Here, BALB/c mice were orally infected with metacyclic trypomastigotes of T. cruzi Tulahuén strain and used to evaluate the cytokine response, primary and secondary hemostasis during acute T. cruzi infection. When compared with control uninfected animals, orally infected mice presented higher pro-inflammatory cytokine (TNF-α, IFN-γ and IL-6) serum levels. The highest concentrations were obtained concomitantly to the increase of parasitemia, between 14-28 days post-infection (dpi). Blood counts in the oral infected group revealed concomitant leukocytosis and thrombocytopenia, the latter resulting in increased bleeding at 21 dpi. Hematological changes paralleled with prolonged activated partial thromboplastin time, Factor VIII consumption and increased D-dimer levels, suggest that oral T. cruzi infection relies on disseminated intravascular coagulation. Remarkably, blockade of the IL-6 receptor blunted hematological abnormalities, revealing a critical role of IL-6 in the course of oral infection. These results unravel that acute T. cruzi oral infection results in significant alterations in the hemostatic system and indicates the relevance of the crosstalk between inflammation and hemostasis in this parasitic disease.